Negative electrode material, preparation method, secondary battery and electric device

By introducing graphite skeleton and porous carbon core into the negative electrode material of lithium-ion batteries and covering it with disordered carbon layer, the upper capacity limit and expansion problems of graphite anode materials in the prior art are solved, and higher energy density and cycling performance are achieved.

CN119764420APending Publication Date: 2025-04-04DONGGUAN AMPEREX TECH +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411997279.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The negative electrode material of existing lithium-ion batteries is close to its theoretical capacity upper limit, making it difficult to further improve the energy density. The expansion of the graphite negative electrode during long cycles leads to material failure and rapid attenuation of capacity.

Method used

A negative electrode material is used, the inner body has a graphite skeleton and a porous carbon core, and is coated with a disordered carbon layer. By introducing porous carbon cores and disordered carbon layer coating into the graphite skeleton, the specific capacity and strength of the material are improved and the expansion of the graphite skeleton is slowed down.

Benefits of technology

It improves the energy density and circulation performance of the secondary battery, extends the service life of the battery, and reduces the expansion effect of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764420A_ABST
    Figure CN119764420A_ABST
Patent Text Reader

Abstract

The invention provides a negative electrode material, a preparation method, a secondary battery and an electric device. According to the negative electrode material in the first aspect of the application, the negative electrode material has an inner main body and a layer structure wrapping the inner main body, and the inner main body has a graphite skeleton and a porous carbon core arranged in the graphite skeleton; and the layer structure is a disordered carbon layer. The disordered carbon layer is used for coating, so that the strength of the material is effectively improved, a surface open pore structure can be converted into a closed pore structure, and the co-intercalation effect of solvent molecules and graphite can be retarded. The porous carbon core is introduced into the graphite skeleton, so that the overall specific capacity of the material can be improved, the expansion of the graphite skeleton is slowed down, and the energy density and the cycle performance of the secondary battery are further improved. The negative electrode material provided by the invention has the characteristics of high specific capacity, low expansion and the like, and when the negative electrode material is applied to a secondary battery, the secondary battery has relatively high energy density and good cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical technology, and in particular to a negative electrode material, a preparation method, a secondary battery and an electrical device. Background Art

[0002] Secondary batteries represented by lithium-ion batteries have outstanding features such as high energy density, long cycle life, low pollution, and no memory effect. As a clean energy source, the application of secondary batteries has gradually spread from electronic products to large-scale devices such as electric vehicles to adapt to the sustainable development strategy of the environment and energy. This also puts forward higher requirements for the energy density of secondary batteries.

[0003] At present, the negative electrode active material of commercial secondary batteries is still mainly graphite. Graphite has advantages such as high conductivity and high stability. However, the theoretical capacity of graphite is about 372mAh / g, and in recent years it has almost been developed to its theoretical capacity limit. The energy density of lithium-ion batteries with graphite as the negative electrode active material is difficult to further improve. In addition, during long cycles, the repeated expansion of the graphite negative electrode often causes material failure, which in turn leads to rapid decay of the capacity of the secondary battery.

[0004] There is an urgent need for a new negative electrode material, preparation method, secondary battery and power-consuming device. Summary of the invention

[0005] In a first aspect, the present application provides a negative electrode material, the negative electrode material having an inner body and a layer structure wrapping the inner body, wherein:

[0006] The inner body has a graphite skeleton and a porous carbon core arranged inside the graphite skeleton;

[0007] The layer structure is a disordered carbon layer.

[0008] In some optional embodiments of the first aspect of the present application, the porous carbon core includes a plurality of porous carbon particles.

[0009] In some optional embodiments of the first aspect of the present application, the porous carbon core is a single porous carbon particle.

[0010] In some optional embodiments of the first aspect of the present application, the graphite skeleton partially covers the single porous carbon particle.

[0011] In some optional embodiments of the first aspect of the present application, the portion of a single porous carbon particle not covered by the graphite skeleton is arranged in contact with the disordered carbon layer.

[0012] In some optional embodiments of the first aspect of the present application, the graphite skeleton completely covers a single porous carbon particle.

[0013] In some optional embodiments of the first aspect of the present application, the porous carbon core contains carbon elements.

[0014] In some optional embodiments of the first aspect of the present application, the porous carbon core also includes other elements, and the other elements include one or more of Ti, Si, B, Zr, Fe, Al, Mo, V, Nb, W, Ta, Cr, Sr, Ba and Ca.

[0015] In some optional embodiments of the first aspect of the present application, the content A of other elements in the porous carbon core is 0<A≤5%.

[0016] In some optional embodiments of the first aspect of the present application, the porous carbon core includes carbides, halides or a mixture of the two compounds of other elements.

[0017] In some optional embodiments of the first aspect of the present application, in the Raman test, the negative electrode material has a Raman shift of 1300 cm -1 Up to 1400cm -1 The region contains a characteristic peak D with a peak intensity of ID and a Raman shift of 1530cm -1 Up to 1630cm -1 The region contains a characteristic peak G with a peak intensity of IG, and the peak intensity ratio ID / IG of the Raman test D peak to G peak satisfies: 0.2≤ID / IG≤0.7.

[0018] In some optional embodiments of the first aspect of the present application, the true density of the negative electrode material is 1.5 g / cm 3 Up to 2.0g / cm 3 .

[0019] In some optional embodiments of the first aspect of the present application, the pore volume of the negative electrode material obtained by carbon dioxide adsorption and desorption test is ≤0.05cm 3 / g.

[0020] In some optional embodiments of the first aspect of the present application, the negative electrode material satisfies at least one of the following conditions:

[0021] (1) The Dv50 of the negative electrode material is 3 μm to 12 μm;

[0022] (2) The specific surface area of ​​the negative electrode material is 0.5 m 2 / g to 50m 2 / g.

[0023] In some optional embodiments of the first aspect of the present application, the Dv50 of the negative electrode material is 5 μm to 9 μm;

[0024] In some optional embodiments of the first aspect of the present application, the specific surface area of ​​the negative electrode material is 0.5 m 2 / g to 5m 2 / g.

[0025] A second aspect of the present application provides a method for preparing a negative electrode material, comprising the following steps:

[0026] S10: All the porous carbon precursor powders to be coated are mixed with the initial asphalt powder to obtain an initial mixed powder, the initial mixed powder is heated to T1 and oxygen-containing gas is introduced to oxidize for t1 time to complete a heating oxidation coating treatment, the treated powder is collected, and the heating oxidation coating treatment is repeated for multiple times, and each time a new portion of asphalt powder is added to the treated powder collected last time, and then heated and oxygen-containing gas is introduced to oxidize, until the oxidized asphalt powder coats the porous carbon precursor powder to a preset coating degree, thereby obtaining an asphalt-coated powder;

[0027] S20: heating the asphalt-coated powder to T2 in an inert atmosphere and then performing heat preservation treatment, cooling the temperature to room temperature in the inert atmosphere after t2 time, to obtain carbonized powder;

[0028] S30: heating the carbonized powder to T3 in an inert atmosphere and then performing heat preservation treatment, and then cooling the temperature to room temperature in the inert atmosphere after the heat preservation time t3 to obtain graphitized powder;

[0029] S40: heating the graphitized powder to T4 under an inert atmosphere and then keeping the temperature, introducing a halogen-containing atmosphere at T4 to perform etching for t4 time, then introducing an inert gas or a mixture of an inert gas and hydrogen to remove impurities, and finally cooling the temperature to room temperature under the inert atmosphere to obtain a graphite composite material containing a porous carbon core;

[0030] S50: heating the graphite composite material to T5 under an inert atmosphere and then keeping the temperature, introducing an organic atmosphere at T5 for t5 time, and finally cooling the graphite composite material under an inert atmosphere to finally collect and obtain the negative electrode material.

[0031] In some optional embodiments of the second aspect of the present application,

[0032] Step S10 includes:

[0033] The encapsulation structure of the inner body in the negative electrode material is controlled by adjusting at least one of the ratio of the Dv50 value of the pitch powder to the Dv50 value of the porous carbon precursor powder, the mass ratio of all porous carbon precursor powders to be encapsulated to all portions of the pitch powder, and the number of heating oxidation encapsulation treatments.

[0034] In some optional embodiments of the second aspect of the present application, the ratio of the Dv50 value of the asphalt powder to the Dv50 value of the porous precursor powder is 0.05 to 0.5.

[0035] In some optional embodiments of the second aspect of the present application, the ratio of the Dv50 value of the asphalt powder to the Dv50 value of the porous carbon precursor powder is greater than 0.5.

[0036] In step S10, the porous carbon precursor powder includes at least one of oxides or carbides of Ti, Si, B, Zr, Fe, Al, Mo, V, Nb, W, Ta, Cr, Sr, Ba, and Ca.

[0037] In some optional embodiments of the second aspect of the present application, the porous carbon precursor powder includes SiO2.

[0038] In some optional embodiments of the second aspect of the present application, the porous carbon precursor powder includes SiC, TiC, B4C or W2C.

[0039] In some optional embodiments of the second aspect of the present application, the porous carbon precursor powder is a nanopowder, and the Dv50 of the porous carbon precursor powder is 0nm to 500nm, excluding the endpoint 0nm.

[0040] In some optional embodiments of the second aspect of the present application, the porous carbon precursor powder is a micron powder, and the Dv50 of the porous carbon precursor powder is 1 μm to 20 μm.

[0041] In some optional embodiments of the second aspect of the present application, in step S10, the asphalt powder Dv50 is 1 μm to 5 μm.

[0042] In some optional embodiments of the second aspect of the present application, in step S10, the porous carbon precursor powder and the asphalt powder are mixed in a mass ratio of 100:1 to 30.

[0043] In some optional embodiments of the second aspect of the present application, in step S10, the temperature T1 is 130° C. to 500° C., and the time t1 is 0.2 h to 12 h.

[0044] In some optional embodiments of the second aspect of the present application, at least one of the following conditions is met:

[0045] (1) In step S20, the temperature T2 is 600° C. to 1300° C., and the time t2 is 0.5 h to 5 h;

[0046] (2) In step S30, the temperature T3 is 2000° C. to 3000° C., and the time t3 is 0.5 h to 12 h;

[0047] (3) In step S40, the temperature T4 is 300° C. to 1500° C., and the time t4 is 0.5 h to 36 h;

[0048] (4) In step S50, the temperature T5 is 400°C to 1000°C, and the time t5 is 0.5h to 36h.

[0049] In some optional embodiments of the second aspect of the present application, in step S40, the halogen-containing atmosphere includes at least one of F2, Cl2, Br2, I2, HF, CCl4, CHCl3, Cl2-H2, Cl2-HCl, and HCl.

[0050] The third aspect of the present application provides a secondary battery, comprising a positive electrode plate, a negative electrode plate and an electrolyte, the negative electrode plate comprising a negative electrode collector and a negative electrode active material layer located on at least one surface of the negative electrode collector, the negative electrode active material layer comprising the negative electrode material of the first aspect of the present application or the negative electrode material prepared by the preparation method of the second aspect of the present application.

[0051] In some embodiments provided in the third aspect of the present application, the compaction density of the negative electrode active material layer is 1.1 g / cm 3 Up to 1.6g / cm 3 .

[0052] A fourth aspect of the present application provides an electrical device, comprising the secondary battery of the third aspect of the present application.

[0053] Beneficial effects:

[0054] The first aspect of the present application provides a negative electrode material, which comprises a disordered carbon layer, a graphite skeleton structure and a porous carbon core. Coating with a disordered carbon layer not only effectively improves the strength of the material, but also converts the surface open-pore structure into a closed-pore structure, and also slows down the co-embedding effect of solvent molecules and graphite. Introducing a porous carbon core into the graphite skeleton can improve the overall specific capacity of the material, slow down the expansion of the graphite skeleton, and further improve the energy density and cycle performance of the secondary battery. The negative electrode material provided by the present application has the characteristics of high specific capacity, low expansion, etc. The application of the negative electrode material in the secondary battery enables the secondary battery to have a higher energy density and good cycle performance.

[0055] The second aspect of the present application provides a method for preparing a negative electrode material. The negative electrode material is prepared by the method provided in the second aspect of the present application. First, an asphalt-coated powder is formed as a precursor of a graphitized powder. The asphalt-coated powder becomes a graphitized powder after carbonization and graphitization. The powder is then etched with a halogen atmosphere to form a graphite composite material containing a porous carbon core. Finally, an organic atmosphere is introduced to form a disordered carbon layer deposited on the surface of the graphite composite material containing a porous carbon core through a high-temperature cracking reaction.

[0056] The porous carbon core has a uniform pore structure, a large pore volume and a suitable pore size, and has a high specific capacity and first coulombic efficiency. Applying its negative electrode material to the negative electrode of a secondary battery can increase the energy density of the secondary battery, while improving the expansion rate of the secondary battery and thus improving the cycle performance.

[0057] The secondary battery provided in the third aspect of the present application has high energy density and first coulombic efficiency and good cycle performance. The negative electrode plate in the secondary battery includes a negative electrode current collector and a negative electrode active material layer located on at least one surface of the negative electrode current collector, and the negative electrode active material layer includes the negative electrode material provided in the first aspect of the present application or the negative electrode material prepared according to the preparation method provided in the second aspect of the present application. The negative electrode plate provided in the third aspect of the present application has high reversible capacity and good kinetic performance. Applying it to a secondary battery can improve the energy density and first coulombic efficiency of the secondary battery and improve the cycle performance of the secondary battery.

[0058] The fourth aspect of the present application provides an electric device, which includes the secondary battery in the third aspect of the present application. The electric device of the present application has a long service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 It is the TEM spectrum of the negative electrode material in the embodiment of the present application. DETAILED DESCRIPTION

[0060] The present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0061] like Figure 1 As shown, the first aspect of the present application provides a negative electrode material, the negative electrode material having an inner body and a layer structure wrapping the inner body, wherein:

[0062] The inner body has a graphite skeleton and a porous carbon core arranged inside the graphite skeleton;

[0063] The layer structure is a disordered carbon layer.

[0064] The first aspect of the present application provides a negative electrode material, which comprises a disordered carbon layer, a graphite skeleton structure and a porous carbon core. Coating with a disordered carbon layer not only effectively improves the strength of the material, but also converts the surface open-pore structure into a closed-pore structure, and also slows down the co-embedding effect of solvent molecules and graphite. Introducing a porous carbon core into the graphite skeleton can improve the overall specific capacity of the material, slow down the expansion of the graphite skeleton, and further improve the energy density and cycle performance of the secondary battery. The negative electrode material provided by the present application has the characteristics of high specific capacity, low expansion, etc. The application of the negative electrode material in the secondary battery enables the secondary battery to have a higher energy density and good cycle performance.

[0065] In some optional embodiments of the first aspect of the present application, the porous carbon core includes a plurality of porous carbon particles. Figure 1 As shown in the schematic diagram of the microstructure in the first form, a plurality of porous carbon particles in the porous carbon core exist in the graphite skeleton in a uniformly dispersed form.

[0066] In some optional embodiments of the first aspect of the present application, the porous carbon core includes a plurality of porous carbon particles. Figure 1 As shown in the microstructure diagram of the second form, at least some of the porous carbon particles in the porous carbon core are bonded together, and some porous carbon particles exist alone. The porous carbon particles in the porous carbon core are dispersed inside the graphite skeleton in a bonded form.

[0067] In some optional embodiments of the first aspect of the present application, the porous carbon core is a single porous carbon particle.

[0068] like Figure 1 As shown in the schematic diagram of the microstructure in the third form, the graphite skeleton completely covers the single porous carbon particle, and the disordered carbon layer is wrapped around the outside of the graphite skeleton. The porous carbon core of the graphite skeleton is separated from the disordered carbon layer.

[0069] like Figure 1 As shown in the schematic diagram of the microstructure in the fourth form, in some optional embodiments of the first aspect of the present application, the graphite skeleton partially covers a single porous carbon particle. In some examples of these embodiments, the single porous carbon particle is not partially covered by the graphite skeleton and is arranged in contact with the disordered carbon layer.

[0070] In these embodiments, the state of the porous carbon precursor powder during the preparation process is one of the important factors that determine the existence form of the porous carbon kernel in the graphite skeleton. The porous carbon-rich pore structure enables the composite material of the present application to have a more considerable gram capacity than the graphite material, and its volume expansion during the charge and discharge process is negligible. The porous carbon is introduced into the graphite in the form of small particles, that is, the porous carbon kernel includes a plurality of porous carbon particles, which can not only improve the capacity of the negative electrode material, but also curb the expansion effect of the graphite material. For porous carbon with a higher gram capacity than graphite, due to its low packing density, its volume specific capacity is often lower than that of graphite. The negative electrode material prepared by coating a single porous carbon particle with a graphite material, the volume of the porous carbon particles is higher, and the gram capacity of the negative electrode material is higher. The slippage of the graphite skeleton on the surface of the composite material during the cold pressing of the pole piece enables the material to have a higher packing density. By controlling the coating process, the prepared porous carbon core exists in the form of a separate particle inside the graphite skeleton and the porous carbon core is incompletely coated with graphite. In this way, some lithium ions can diffuse into the porous carbon without passing through the graphite, and the negative electrode material has a better lithium ion diffusion ability.

[0071] In some optional embodiments of the first aspect of the present application, the porous carbon core contains carbon elements.

[0072] In some optional embodiments of the first aspect of the present application, the porous carbon core also includes other elements, and the other elements include one or more of Ti, Si, B, Zr, Fe, Al, Mo, V, Nb, W, Ta, Cr, Sr, Ba and Ca.

[0073] In some optional embodiments of the first aspect of the present application, the content A of other elements in the porous carbon core is 0<A≤5%.

[0074] In some optional embodiments of the first aspect of the present application, the porous carbon core includes carbides, halides or a mixture of the two compounds of other elements.

[0075] In some embodiments, carbides of other elements include at least one of SiC, TiC, ZrC, V2C, NbC, Nb2C, TaC, Ta2C, Cr3C2, Mo2C, MoC, W2C, WC, BaC2, CaC2, SrC2, Al4C3, B4C, Fe3C, Ti3AlC2, Ti2AlC, Ti3AlCN, V2AlC, Nb2AlC, and Ti3C2.

[0076] In some other embodiments, the halides of other elements include at least one of Ti, Si, B, Zr, Fe, Al, Mo, V, Nb, W, Ta, Cr, and Sr halides.

[0077] A porous carbon core is introduced inside the negative electrode material, and its pore structure has lithium storage activity, which effectively improves the overall specific capacity of the negative electrode material. In addition, the introduction of other elements can further enhance the strength of the material, help prevent material breakage and failure, and improve the cycle performance of secondary batteries.

[0078] In the Raman test, the negative electrode material has a Raman shift of 1300 cm -1 Up to 1400cm -1 The region contains a characteristic peak D with a peak intensity of ID and a Raman shift of 1530cm -1 Up to 1630cm -1 The region contains a characteristic peak G with a peak intensity of IG. The peak intensity ratio of the D peak to the G peak in the Raman test ID / IG satisfies: 0.2≤ID / IG≤0.7. The Raman characteristic D / G ratio of the negative electrode material is in the range of 0.2 to 0.7, indicating that the surface of the negative electrode material is mainly characterized by graphite. Using graphite material as the negative electrode material skeleton and including porous carbon can effectively improve the compaction density of the negative electrode active material layer in the cold pressing process.

[0079] In some optional embodiments of the first aspect of the present application, the true density of the negative electrode material is 1.5 g / cm 3 Up to 2.0g / cm 3The true density of the negative electrode material is 1.5g / cm 3 To 2.0g / cm3, it shows that there are a large number of pores in the porous carbon core of the negative electrode material, which can not only provide more lithium storage sites, but also alleviate the expansion effect of the negative electrode material.

[0080] In some optional embodiments of the first aspect of the present application, the pore volume of the negative electrode material obtained by carbon dioxide desorption test is ≤0.05cm 3 / g, specific surface area is 0.5m 2 / g to 50m 2 / g.

[0081] In some optional embodiments of the first aspect of the present application, the specific surface area of ​​the negative electrode material is 0.5 m 2 / g to 5m 2 / g.

[0082] In these embodiments, the pore volume is calculated using the DFT model. The specific surface area is obtained by nitrogen adsorption and desorption test, and the specific surface area is calculated using the BJH model. The pore volume obtained by the adsorption and desorption test of the negative electrode material is ≤ 0.05 cm 3 / g, specific surface area is 0.5m 2 / g to 50m 2 / g, indicating that the disordered carbon layer on the outside of the negative electrode material effectively wraps the graphite skeleton and / or the exposed porous carbon core inside, which is beneficial to improving the first coulombic efficiency of the secondary battery and improving the cycle performance of the secondary battery.

[0083] In some optional embodiments of the first aspect of the present application, the Dv50 of the negative electrode material is 3 μm to 12 μm.

[0084] In some optional embodiments of the first aspect of the present application, Dv50 of the negative electrode material is 5 μm to 9 μm.

[0085] In these embodiments, by regulating the Dv50 of the negative electrode material within the above range, the negative electrode material particles have a relatively dense stacking density and a relatively fast charge and discharge speed, and the negative electrode material is applied to the secondary battery, which is beneficial to improving the energy density and fast charge and discharge capability of the secondary battery.

[0086] A second aspect of the present application provides a method for preparing a negative electrode material, comprising the following steps:

[0087] S10: All the porous carbon precursor powders to be coated are mixed with the initial asphalt powder to obtain the initial mixed powder, the initial mixed powder is heated to T1 and oxygen-containing gas is introduced to oxidize for t1 time to complete a heating oxidation coating treatment, the treated powder is collected, and the heating oxidation coating treatment is repeated for multiple times, and each time a new portion of asphalt powder is added to the treated powder collected last time, and then heated and oxygen-containing gas is introduced to oxidize until the oxidized asphalt powder coats the porous carbon precursor powder to a preset coating degree, thereby obtaining asphalt-coated powder; porous carbon precursor powder porous carbon precursor powder

[0088] S20: heating the asphalt-coated powder to T2 in an inert atmosphere and then performing heat preservation treatment, and cooling the temperature to room temperature in an inert atmosphere after heat preservation for t2 time to obtain carbonized powder;

[0089] S30: heating the carbonized powder to T3 in an inert atmosphere and then performing heat preservation treatment, and cooling the temperature to room temperature in the inert atmosphere after heat preservation for t3 time to obtain graphitized powder;

[0090] S40: heating the graphitized powder to T4 under an inert atmosphere and then keeping the temperature, introducing a halogen-containing atmosphere at T4 to perform etching for t4 time, then introducing an inert gas or a mixture of an inert gas and hydrogen to remove impurities, and finally cooling the temperature to room temperature under the inert atmosphere to obtain a graphite composite material containing a porous carbon core;

[0091] S50: heating the graphite composite material to T5 under an inert atmosphere and then keeping the temperature, introducing an organic atmosphere at T5 for t5 time, and finally cooling the graphite composite material under an inert atmosphere to finally collect and obtain the negative electrode material.

[0092] Step S10 includes:

[0093] The encapsulation structure of the inner body in the negative electrode material is controlled by adjusting at least one of the ratio of the Dv50 value of the pitch powder to the Dv50 value of the porous carbon precursor powder, the mass ratio of all porous carbon precursor powders to be encapsulated to all portions of the pitch powder, and the number of heating oxidation encapsulation treatments.

[0094] In these embodiments, all portions of asphalt powder refer to the total amount of asphalt powder added in step S10.

[0095] The oxidized asphalt powder coats the porous carbon precursor powder to a preset coating degree, and the preset coating degree can be obtained through TEM electron microscope characterization observation.

[0096] In some optional embodiments of the second aspect of the present application, the ratio of the Dv50 value of the asphalt powder to the Dv50 value of the porous precursor powder is 0.05 to 0.5. In these embodiments, it is more effective to ensure that the asphalt powder is melted and coated on the surface of the porous precursor powder each time the heating oxidation coating treatment is performed, and no adhesion occurs, thereby ensuring a uniform and thin coating effect.

[0097] In some optional embodiments of the second aspect of the present application, the ratio of the Dv50 value of the asphalt powder to the Dv50 value of the porous carbon precursor powder is greater than 0.5. In these embodiments, the asphalt powder is easily melted to completely cover the porous carbon precursor powder, and further treated in a halogen atmosphere to obtain a negative electrode material having a structure in which porous carbon is dispersed in the form of multiple small particles inside a graphite skeleton.

[0098] In some optional embodiments of the second aspect of the present application, new asphalt powder is added when the heating oxidation coating treatment steps are repeated, that is, the total asphalt powder (also referred to as all parts of asphalt powder) is added in multiple times. Each heating oxidation treatment can make the asphalt powder melt and coat the carbide surface more thinly, and the asphalt powders do not stick together, so the coating effect can be effectively controlled.

[0099] In some examples, controlling the number of repetitions of the heating oxidation and wrapping treatment step can obtain a negative electrode material in which a graphite skeleton completely covers a single porous carbon particle or a negative electrode material in which a graphite skeleton does not completely cover a single porous carbon particle. Of course, in other examples, in addition to controlling the number of repetitions of the heating oxidation and wrapping treatment step, it is also necessary to control the ratio of the Dv50 value of the asphalt powder to the Dv50 value of the porous carbon precursor powder.

[0100] In some optional embodiments of the second aspect of the present application, in step S10, the porous carbon precursor powder includes at least one of oxides or carbides of Ti, Si, B, Zr, Fe, Al, Mo, V, Nb, W, Ta, Cr, Sr, Ba, and Ca elements.

[0101] In some optional embodiments of the second aspect of the present application, the porous carbon precursor powder is a nano powder, and the Dv50 of the porous carbon precursor powder is 0nm to 500nm, excluding the endpoint 0nm. In some optional embodiments of the second aspect of the present application, the porous carbon precursor powder is a micron powder, and the Dv50 of the porous carbon precursor powder is 1nm to 20μm.

[0102] In some optional embodiments of the second aspect of the present application, in step S10, the asphalt powder Dv50 is 1 μm to 5 μm.

[0103] In some optional embodiments of the second aspect of the present application, in the step S10, the porous carbon precursor powder and the asphalt powder are mixed in a mass ratio of 100:1 to 30.

[0104] In some optional embodiments of the second aspect of the present application, in step S10, the temperature T1 is 130° C. to 500° C., and the time t1 is 0.2 h to 12 h.

[0105] In some optional embodiments of the second aspect of the present application, in step S10, the temperature T1 is 130° C. to 500° C., and the time t1 is 0.2 h to 12 h.

[0106] In some optional embodiments of the second aspect of the present application, at least one of the following conditions is met:

[0107] (1) In step S20, the temperature T2 is 600° C. to 1300° C., and the time t2 is 0.5 h to 5 h;

[0108] (2) In step S30, the temperature T3 is 2000° C. to 3000° C., and the time t3 is 0.5 h to 12 h;

[0109] (3) In step S40, the temperature T4 is 300° C. to 1500° C., and the time t4 is 0.5 h to 36 h;

[0110] (4) In step S50, the temperature T5 is 400°C to 1000°C, and the time t5 is 0.5h to 36h.

[0111] In some optional embodiments of the second aspect of the present application, in step S40, the halogen-containing atmosphere includes at least one of F2, Cl2, Br2, I2, HF, CCl4, CHCl3, Cl2-H2, Cl2-HCl, and HCl.

[0112] In some optional embodiments of the second aspect of the present application, the organic atmosphere is at least one of methane, ethylene, acetylene and propane, or the organic atmosphere is a mixture of at least one of methane, ethylene, acetylene and propane and argon.

[0113] In some optional embodiments of the second aspect of the present application, the inert atmosphere is at least one of nitrogen, argon or helium.

[0114] The second aspect of the present application provides a method for preparing a negative electrode material. The negative electrode material is prepared by the method provided in the second aspect of the present application. First, an asphalt-coated powder is formed as a precursor of a graphitized powder. The asphalt-coated powder becomes a graphitized powder after carbonization. The powder is then etched with a halogen atmosphere to form a graphite composite material containing a porous carbon core. Finally, an organic atmosphere is introduced to deposit a disordered carbon layer on the surface of the graphite composite material containing a porous carbon core through a high-temperature cracking reaction.

[0115] The porous carbon core has a uniform pore structure, a large pore volume and a suitable pore size, and has a high specific capacity and first coulombic efficiency. Applying its negative electrode material to the negative electrode of a secondary battery can increase the energy density of the secondary battery, while improving the expansion rate of the secondary battery and thus improving the cycle performance.

[0116] The third aspect of the present application provides a secondary battery, including a negative electrode plate. The secondary battery provided in the third aspect of the present application has high energy density and first coulombic efficiency and good cycle performance.

[0117] The negative electrode plate in the secondary battery of the third aspect of the present application comprises a negative electrode current collector and a negative electrode active material layer located on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer comprises the negative electrode material of the first aspect of the present application or the negative electrode material prepared by the preparation method of the second aspect of the present application.

[0118] In some optional embodiments of the third aspect of the present application, the compaction density of the negative electrode active material layer is 1.1 g / cm 3 Up to 1.6g / cm 3 .

[0119] In some optional embodiments of the third aspect of the present application, the negative electrode plate comprises a negative electrode current collector and a negative electrode active material layer located on at least one surface of the negative electrode current collector, and the negative electrode active material layer comprises the negative electrode material provided in the first aspect of the present application or the negative electrode material prepared according to the preparation method provided in the second aspect of the present application. The negative electrode plate in the third aspect of the present application has high reversible capacity and good kinetic performance. Applying it to a secondary battery can improve the energy density and first coulomb efficiency of the secondary battery and improve the cycle performance of the secondary battery.

[0120] In one embodiment of the present application, the negative electrode active material layer may include other negative electrode active materials, such as artificial graphite, in addition to the negative electrode material. By mixing the negative electrode material with other negative electrode active materials, it is beneficial to increase the compaction density of the negative electrode active material layer, thereby increasing the energy density of the secondary battery.

[0121] The present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the negative electrode current collector may include a metal foil, a porous metal plate or a composite current collector. The metal foil includes copper foil, copper alloy foil, nickel foil, stainless steel foil or titanium foil, the porous metal plate includes nickel foam or copper foam, etc., and the composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector can be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.). In the present application, there is no particular restriction on the thickness of the negative electrode current collector and the negative electrode active material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4 μm to 12 μm, and the thickness of the single-sided negative electrode active material layer is 30 μm to 200 μm. In the present application, the negative electrode active material layer can be arranged on one surface in the thickness direction of the negative electrode current collector, or on two surfaces in the thickness direction of the negative electrode current collector. It should be noted that the "surface" here can be the entire area of ​​the negative electrode current collector or a partial area of ​​the negative electrode current collector. This application is not particularly limited as long as the purpose of this application can be achieved. The negative electrode active material layer of the present application may also include a conductive agent and a negative electrode binder. This application has no special restrictions on the conductive agent and the negative electrode binder in the negative electrode active material layer, as long as the purpose of this application can be achieved. For example, the conductive agent may include but is not limited to carbon materials, metals or conductive polymers. The carbon material may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. The metal may include metal powder or metal fiber of copper, iron, aluminum, etc. The conductive polymer may include a polyphenylene derivative. The negative electrode binder may include but is not limited to polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene 1,1-difluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin or nylon. Optionally, the negative electrode active material layer also includes a thickener, which may include but is not limited to sodium carboxymethyl cellulose.

[0122] The negative electrode sheet in the embodiment of the present application can be prepared according to conventional methods in the art. For example, the negative electrode material or the negative electrode material and other optional negative electrode active materials, conductive agent, negative electrode binder and thickener are dispersed in a solvent, and the solvent can be N-methylpyrrolidone (NMP) or deionized water to form a uniform negative electrode slurry, and the negative electrode slurry is coated on the negative electrode current collector, and the negative electrode sheet is obtained through drying, cold pressing and other processes.

[0123] The negative electrode sheet in the embodiment of the present application does not exclude other additional functional layers in addition to the negative electrode active material layer. For example, in one embodiment, the negative electrode sheet of the present application also includes a conductive primer layer (for example, composed of a conductive agent and a negative electrode binder) sandwiched between the negative electrode current collector and the negative electrode active material layer and disposed on the surface of the negative electrode current collector. In another embodiment, the negative electrode sheet of the present application also includes a protective layer covering the surface of the negative electrode active material layer.

[0124] The secondary battery provided in the third aspect of the present application has high energy density and first coulombic efficiency as well as good cycle performance.

[0125] The secondary battery of the present application also includes a positive electrode sheet. The present application has no special restrictions on the positive electrode sheet, as long as the purpose of the present application can be achieved. For example, the positive electrode sheet includes a positive current collector and a positive active material layer arranged on at least one surface of the positive current collector. The present application has no special restrictions on the positive current collector, as long as the purpose of the present application can be achieved. For example, the positive current collector may include a metal foil or a composite current collector, etc. For example, the metal foil is an aluminum foil. The composite current collector may include a polymer material base layer and a metal material layer located on at least one surface of the polymer material base layer. For example, the material of the metal material layer may include at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver or silver alloy. The polymer material base layer may include at least one of polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene or polyethylene. The positive active material layer of the present application includes a positive active material. The present application has no special restrictions on the type of positive active material, as long as the purpose of the present application can be achieved, and it can be selected according to actual needs.

[0126] In some embodiments, the secondary battery is a lithium ion battery, and the positive electrode active material may include a lithium transition metal oxide, which may include but is not limited to lithium nickel cobalt manganese oxide (LiNi 0.90 Co 0.05 Mn 0.05 O2 (NCM955), NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganate, lithium iron manganese phosphate or lithium titanate. In other embodiments, the secondary battery is a sodium ion battery, and the positive electrode active material may include at least one of a sodium transition metal oxide, a polyanionic compound and a Prussian blue compound. The sodium transition metal oxide may include Na1-xCu h Fe k Mn l M1mO2-y、Na 0.67 Mn 0.7 Ni z M20.3 -zO2、Na a Li b Ni c Mn d Fe e O2, wherein M1 is at least one of Li, Be, B, Mg, Al, K, Ca, Ti, Co, Ni, Zn, Ga, Sr, Y, Nb, Mo, In, Sn or Ba, 0<x≤0.33, 0<h≤0.24, 0≤k≤0.32, 0<l≤0.68, 0≤m<0.1, h+k+l+m=1, 0≤y<0.2; M2 is at least one of Li, Mg, Al, Ca, Ti, Fe, Cu, Zn or Ba, 0<z≤0.1; 0.67<a≤1, 0<b<0.2, 0<c<0.3, 0.67<d+e<0.8, b+c+d+e=1. The polyanionic compound may include but is not limited to: A1 f M3g(PO4) i O j X13-j、Na n M4PO4X2、Na p M5 q (SO4)3、Na s Mn t Fe3-t(PO4)2(P2O7), wherein A1 is at least one of H, Li, Na, K or NH4, M3 is at least one of Ti, Cr, Mn, Fe, Co, Ni, V, Cu or Zn, X1 is at least one of F, Cl or Br, 0<f≤4, 0<g≤2, 1≤i≤3, 0≤j≤2; M4 is at least one of Mn, Fe, Co, Ni, Cu or Zn, X2 is at least one of F, Cl or Br, 0<n≤2; M5 is at least one of Mn, Fe, Co, Ni, Cu or Zn, 0<p≤2, 0<q≤2; 0<s≤4, 0≤t≤3. Prussian blue compounds may include but are not limited to A2uM6 v [M7(CN)6]w·xH2O, where A2 is H + NH4 + , alkali metal cations and alkaline earth metal cations, M6 and M7 are each independently at least one of transition metal cations, 0<u≤2, 0<v≤1, 0<w≤1, 0<x<6. For example, A2 is H + , Li + 、Na + , K + NH4 + , Rb + , Cs + , Fr + 、Be 2+Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ and Ra 2+ M6 and M7 are each independently a cation of at least one transition metal element selected from Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Sn and W. Preferably, A2 is Li + 、Na + and K + At least one of Mn, Fe, Co, Ni and Cu, M6 is a cation of at least one transition metal element selected from the group consisting of Mn, Fe, Co, Ni and Cu, and M7 is a cation of at least one transition metal element selected from the group consisting of Mn, Fe, Co, Ni and Cu.

[0127] The present application has no particular restrictions on the thickness of the positive current collector and the positive active material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the positive current collector is 5μm to 20μm, preferably 6μm to 18μm. The thickness of the single-sided positive active material layer is 30μm to 400μm. In the present application, the positive active material layer can be arranged on one surface in the thickness direction of the positive current collector, or on two surfaces in the thickness direction of the positive current collector. It should be noted that the "surface" here can be the entire area of ​​the positive current collector or a partial area of ​​the positive current collector. The present application has no particular restrictions, as long as the purpose of the present application can be achieved. The positive active material layer of the present application may also include a conductive agent and a positive electrode binder. The present application has no particular restrictions on the type of conductive agent in the positive active material layer, as long as the purpose of the present application can be achieved. For example, the conductive agent may be the same type of conductive agent as in the above-mentioned negative active material layer. The present application has no particular restrictions on the type of positive electrode binder in the positive active material layer, as long as the purpose of the present application can be achieved. For example, the positive electrode binder may be of the same type as the negative electrode binder in the negative electrode active material layer. The present application does not particularly limit the mass ratio of the positive electrode active material, the conductive agent, and the positive electrode binder in the positive electrode active material layer. Those skilled in the art can prepare the positive electrode sheet in the present application according to conventional methods in the art based on actual conditions. For example, the positive electrode active material layer is usually formed by coating the positive electrode slurry on the positive electrode collector, drying, and cold pressing. The positive electrode slurry is usually formed by dispersing the positive electrode active material, the optional conductive agent, the optional positive electrode binder, and any other components in a solvent and stirring them evenly. The solvent may be N-methylpyrrolidone (NMP), but is not limited thereto.

[0128] The positive electrode sheet of the present application does not exclude other additional functional layers in addition to the positive electrode active material layer. For example, in one embodiment, the positive electrode sheet of the present application also includes a conductive primer layer (for example, composed of a conductive agent and a binder) sandwiched between the positive electrode current collector and the positive electrode active material layer and disposed on the surface of the positive electrode current collector. In another embodiment, the positive electrode sheet of the present application also includes a protective layer covering the surface of the positive electrode active material layer.

[0129] The secondary battery of the present application also includes an electrolyte. In one embodiment, the electrolyte may include an organic solvent, an electrolyte salt and an optional additive, and the types of organic solvents, lithium salts and additives are not specifically limited and can be selected according to demand. In one embodiment, the secondary battery is a lithium ion battery, and the electrolyte salt may include a lithium salt, and the lithium salt may include but is not limited to lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalate borate (LiDFOB), lithium dioxalate borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalate phosphate) (LiDFOP) or lithium tetrafluorooxalate phosphate (LiTFOP) at least one. The present application does not particularly limit the concentration of lithium salts in the electrolyte, as long as the purpose of the present application can be achieved. In another embodiment, the secondary battery is a sodium ion battery, and the electrolyte salt may include a sodium salt, which may include but is not limited to at least one of NaPF6, NaClO4, NaBCl4, NaSO3CF3 or Na(CH3)C6H4SO3. The present application has no particular limitation on the concentration of the sodium salt in the electrolyte, as long as the purpose of the present application can be achieved.

[0130] The present application has no particular restrictions on organic solvents, as long as the purpose of the present application can be achieved, for example, it may include but is not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other non-aqueous organic solvents. The above-mentioned carbonate compounds may include but are not limited to at least one of linear carbonate compounds, cyclic carbonate compounds or fluorinated carbonate compounds. The above-mentioned linear carbonate compounds may include but are not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or ethyl methyl carbonate (MEC). The above-mentioned cyclic carbonate may include but is not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The fluorinated carbonate compound may include, but is not limited to, at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include, but is not limited to, at least one of methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), n-propyl acetate, tert-butyl acetate, methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), ethyl butyrate (EB), 1,4-butyrolactone (GBL), decalactone, valerolactone, or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other non-aqueous organic solvents may include but are not limited to at least one of dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), diethyl sulfone (ESE), sulfolane (SF), 1,2-dioxolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate.

[0131] In one embodiment, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature or low temperature performance, etc. The additives may include, but are not limited to, at least one of fluoroethylene carbonate (FEC), vinylene carbonate (VC), vinyl carbonate (VEC), diethylene sulfate (DTD), propylene sulfate, vinyl sulfite (ES), 1,3-propane sultone (PS), 1,3-propylene sultone (PST), sulfonate cyclic quaternary ammonium salt, succinic anhydride, succinonitrile (SN), adiponitrile (AND), tris(trimethylsilyl) phosphate (TMSP), and tris(trimethylsilyl) borate (TMSB).

[0132] The electrolyte can be prepared according to conventional methods in the art. For example, an organic solvent, an electrolyte salt, and an optional additive can be mixed uniformly to obtain an electrolyte. There is no particular restriction on the order of adding the materials. For example, the electrolyte salt and the optional additive are added to the organic solvent and mixed uniformly to obtain the electrolyte; or, the electrolyte salt is first added to the organic solvent, and then the optional additive is added to the organic solvent and mixed uniformly to obtain the electrolyte.

[0133] The secondary battery of the present application also includes a diaphragm to separate the positive electrode plate and the negative electrode plate, prevent the internal short circuit of the secondary battery, allow the electrolyte ions to pass freely, and do not affect the electrochemical charge and discharge process. The present application has no special restrictions on the diaphragm, as long as the purpose of the present application can be achieved. For example, the material of the diaphragm may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (such as polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid. At least one of the diaphragm. The type of diaphragm may include at least one of a woven membrane, a non-woven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spinning membrane. The diaphragm of the present application may have a porous structure, and the present application has no special restrictions on the size of the pore size of the porous structure of the diaphragm, as long as the purpose of the present application can be achieved. For example, the size of the pore size can be 0.01 μm to 1 μm. The present application has no special restrictions on the thickness of the diaphragm, as long as the purpose of the present application can be achieved. For example, the thickness of the diaphragm can be 3 μm to 20 μm.

[0134] The secondary battery of the present application also includes an outer packaging for accommodating a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, as well as other components known in the art in the secondary battery, and the present application does not limit the above-mentioned other components. The present application has no particular restrictions on the outer packaging, as long as the purpose of the present application can be achieved. In one embodiment, the outer packaging can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. In another embodiment, the outer packaging can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, for example, the plastic can include but is not limited to at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).

[0135] The secondary battery of the present application is not particularly limited, and may include any device that undergoes an electrochemical reaction. In one embodiment of the present application, the secondary battery may include, but is not limited to, a lithium-ion battery, a sodium-ion battery, a lithium polymer secondary battery, or a lithium-ion polymer secondary battery. The present application does not particularly limit the shape of the secondary battery, and it may be cylindrical, square, or any other shape.

[0136] The preparation process of the secondary battery of the present application is well known to those skilled in the art, and the present application has no special restrictions. For example, it may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly of a winding structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a secondary battery; or stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly of a stacked structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a secondary battery. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the packaging bag as needed to prevent the pressure inside the secondary battery from rising and overcharging and discharging.

[0137] The fifth aspect of the present application provides an electric device, comprising the secondary battery of the fourth aspect of the present application. The fifth aspect of the present application provides an electric device, comprising the secondary battery of the fourth aspect of the present application. The electric device of the present application has a long service life.

[0138] The electric device of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. For example, the electric device can include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery, and a lithium-ion capacitor. [Specific embodiment]

[0140] The following specific examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.

[0141] 1. Test methods and equipment:

[0142] 1.1 Negative electrode sampling method:

[0143] The lithium-ion battery discharged at 0.2C to 2.0V was disassembled, the negative electrode sheet was taken out, and it was soaked in dimethyl carbonate (DMC) for 20 minutes, and then rinsed with DMC and acetone in turn. Then the negative electrode sheet was placed in an oven and baked at 80°C for 12 hours to obtain the treated negative electrode sheet sample. The negative electrode sheet samples in the following compaction density PD test of the negative active material layer were sampled using the above method.

[0144] 1.2 Gram capacity and first efficiency test of negative electrode materials:

[0145] The negative electrode material, binder styrene-butadiene rubber and sodium carboxymethyl cellulose (CMC-Na) were mixed in a mass ratio of 97:1.5:1.5, and then deionized water was added as a solvent and stirred evenly to prepare a negative electrode slurry with a solid content of 40wt%. The negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 10μm, and dried at 85℃ to obtain a negative electrode sheet; the negative electrode sheet was cut into a disc with a diameter of 14mm and used as a working electrode, a metal lithium sheet was used as a counter electrode, and a polyethylene (PE) film with a thickness of 7μm was used as a separator, and a button cell was assembled after injecting the test electrolyte. The button cell was charged and discharged in cycles. The button cell was first discharged to 0mV at 0.05C, and then discharged to 20μA at a constant voltage of 0mV, and the first discharge specific capacity of the button cell was recorded; then charged to 2.5V at a constant current of 0.05C, and the first charge specific capacity of the button cell was recorded. The mass of the negative electrode material in the negative electrode plate is calculated according to the coating weight and area of ​​the negative electrode slurry in the above-mentioned electrode plate preparation process. First efficiency = first charge specific capacity / first discharge specific capacity × 100%; negative electrode material gram capacity Q = first charge specific capacity / mass of negative electrode material, in units of mAh / g. The gram capacity-voltage curve is differentiated to obtain the dQ / dV curve, and the number of reversible lithium insertion peaks and reversible lithium desorption peaks of the measured negative electrode plate in the voltage range of 0V to 0.4V is recorded. Among them, the specific parameters and steps for the preparation of the test electrolyte are the same as those of the electrolyte in Example 1.

[0146] 1.3 Negative electrode material pore volume test:

[0147] The pore volume of the external pore structure of the negative electrode material is tested by the ASAP2460-physical adsorption analyzer. Specifically, after the negative electrode material to be tested is dried and degassed, the adsorption amount of the test gas nitrogen by the negative electrode material under different pressures is tested by the ASAP2460-physical adsorption analyzer, and the adsorption and desorption isotherms are drawn. The shape of the pore is determined according to the shape of the hysteresis loop, and the pore size distribution curve of the micropores is fitted using the DFT model to obtain the pore volume V of the external pore structure of the negative electrode material.

[0148] 1.4 True density test of negative electrode material:

[0149] According to the standard "GB / T24586-2009 Determination of apparent density, true density and porosity of iron ore", the true density of the negative electrode material under test is tested by a true density meter.

[0150] 1.5 Raman test of negative electrode materials:

[0151] The ratio of ID / IG of the negative electrode material has a well-known meaning in the art and can be determined by methods known in the art. For example, using Raman spectroscopy testing, a laser microscopic confocal Raman spectrometer is used to test the surface defectivity of the sample. An area of ​​100 μm × 100 μm is selected on the negative electrode active material layer, and a laser microscopic confocal Raman spectrometer (Raman, HR Evolution, HORIBA Scientific Instrument Division) is used to scan the particles within the area to obtain the D peak and G peak of all particles within the area. The data is processed using LabSpec software to obtain the peak intensities of the D peak and G peak of each particle, which are ID and IG, respectively. The laser wavelength of the Raman spectrometer can be in the range of 532 nm to 785 nm. The value of ID / IG in the text is the average value of the ID and IG ratios of all particles measured within the range.

[0152] 1.6 Dv50 test of negative electrode material:

[0153] The negative electrode material to be tested was taken, and the particle size distribution of the negative electrode material was determined using a laser particle size analyzer (Malvern, UK, model: Mastersizer 2000E) according to GB / T 19077-2016 Particle Size Distribution Laser Diffraction Method.

[0154] 1.7 Specific surface area test of negative electrode material:

[0155] The negative electrode material to be tested was dried in a vacuum drying oven and then placed in a sample tube. The specific surface area S of the negative electrode material to be tested was tested by nitrogen adsorption / desorption method using a specific surface area analyzer (TristarⅡ3020M). The specific test was conducted in accordance with GB / T 19587-2017 Determination of Specific Surface Area of ​​Solid Substances by Gas Adsorption BET Method.

[0156] 1.8 Element analysis test:

[0157] The mass ratio a of the element with a larger relative atomic mass to carbon in the negative electrode material is obtained by using an inductively coupled plasma optical emission spectrometer (ICP-OES) to test. Weigh 0.5 g of the negative electrode material to be tested, add 10 mL of concentrated HNO3 to mix, use microwave digestion, and introduce the digested solution into an inductively coupled photoelectron (ICP) light source. The ICP-OES device detects the content of different substances based on the characteristic radiation energy emitted by the radiation transition when the outer electrons of the gaseous atoms in the sample substance return from the excited state to the ground state after being excited.

[0158] 1.9X-ray diffraction (XRD) test:

[0159] The test method of the diffraction peak of the crystal surface of the negative electrode material is as follows: X-ray powder diffractometer (XRD, instrument model: BrukerD8 ADVANCE) is used for testing, the target material is Cu Kα; the voltage and current are 40KV / 40mA, the scanning angle range is 5° to 80°, the scanning step length is 0.00836°, and the time for each step is 0.3s. The existence form of other elements is determined by comparing with the PDF spectrum of the standard material.

[0160] 1.10 Energy density test:

[0161] Take 5 lithium-ion batteries from each group to be tested, and perform the first charge and discharge in an environment of 25°C. Perform constant current and constant voltage charging at a charging current of 0.5C until the upper limit voltage is reached, and then perform constant current discharge to 3.0V at a discharge current of 0.2C to obtain the discharge capacity and average discharge voltage of the lithium-ion battery, and measure the length, width and thickness of each lithium-ion battery at 50% SOC to calculate the volume of the lithium-ion battery, and calculate the volume energy density of the lithium-ion battery = discharge capacity of the lithium-ion battery × average discharge voltage of the lithium-ion battery / volume of the lithium-ion battery, and further calculate the energy density percentage of each embodiment and comparative example relative to comparative example 1.

[0162] Among them, the upper limit charging voltage of the lithium ion battery whose negative electrode active material includes graphite is 4.48V, and the discharge cut-off voltage is 3.0V; the upper limit charging voltage of the lithium ion battery of the embodiment in which the negative electrode active material is only the negative electrode material is 4.53V, and the discharge cut-off voltage is 2.0V.

[0163] 1.11 Cycle performance test:

[0164] Take 5 lithium-ion batteries from each group of tested batteries, repeatedly charge and discharge the lithium-ion batteries through the following steps, and calculate the discharge capacity retention rate of the lithium-ion batteries.

[0165] The first charge and discharge were carried out in an environment of 25°C. Constant current charging was carried out at a charging current of 1C until the upper limit voltage was reached and then constant voltage charging was switched. Then constant current discharge was carried out at a discharge current of 1C until the discharge cut-off voltage was reached. The discharge capacity of the first cycle was recorded. Then 800 charge and discharge cycles were carried out and the discharge capacity of the 800th cycle was recorded. Among them, the upper limit voltage of charging of lithium-ion batteries containing graphite as the negative electrode active material is 4.48V, and the discharge cut-off voltage is 3.0V; the upper limit voltage of charging of lithium-ion batteries containing only negative electrode materials as the negative electrode active material is 4.53V, and the discharge cut-off voltage is 2.0V.

[0166] Cycle capacity retention rate (%) = (discharge capacity at the 1000th cycle / discharge capacity at the first cycle) × 100%.

[0167] Cycle expansion ratio (%) = (cell thickness at the 1000th cycle / cell thickness at the first cycle) × 100%.

[0168] 2. Preparation of batteries in embodiments and comparative examples

[0169] [Example 1]

[0170] <Preparation of negative electrode materials>

[0171] (1) 20 g SiO2 (particle size 1 μm) powder and 4 g asphalt powder (particle size 2 μm) were mixed in a V-type mixer for 2 h. After mixing, the powder was placed in a heating furnace and heated to 200 °C. Air was introduced and oxidized for 30 min, and then the powder was collected. The above steps were repeated 3 times to obtain asphalt-coated SiO2 powder;

[0172] (The repeated steps are: add 4g of asphalt powder (particle size 2μm) to the powder collected at the end of the last heating oxidation coating and mix with a V-type mixer for 2h. After mixing, the powder is placed in a heating furnace and heated to 200℃, air is introduced, oxidized for 30min, and then the powder is collected).

[0173] (2) placing the asphalt-coated powder in a box furnace and heating it to 1000°C in a nitrogen atmosphere for insulation, treating it at 1000°C for 2 h, and finally cooling it in a nitrogen atmosphere to collect and obtain carbonized powder;

[0174] (3) placing the carbonized powder in a graphitization furnace and heating it to 2800° C. in a nitrogen atmosphere for insulation, treating it at 2800° C. for 1 h, and finally cooling it in a nitrogen atmosphere to collect and obtain graphitized powder;

[0175] (4) placing the graphitized powder in a rotary kiln and heating it to 900° C. in a nitrogen atmosphere for heat preservation, introducing a chlorine atmosphere at 900° C. for etching for 6 h, then cooling it in an inert atmosphere, and collecting a graphite composite material containing a porous carbon core;

[0176] (5) placing the graphite composite material in a rotary kiln, heating it to 600°C in a nitrogen atmosphere and keeping it warm, introducing a 50% acetylene atmosphere at 600°C for 1.5 hours, and finally cooling it in a nitrogen atmosphere to finally collect and obtain the negative electrode material.

[0177] <Preparation of negative electrode sheet>

[0178] The negative electrode material, binder styrene-butadiene rubber and sodium carboxymethyl cellulose (CMC-Na) prepared above are mixed in a mass ratio of 97:1.5:1.5, and then deionized water is added as a solvent and stirred evenly to prepare a negative electrode slurry with a solid content of 40wt%. The negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 6μm, and dried at 85°C to obtain a negative electrode sheet with a single-sided negative electrode active material layer coated with a negative electrode active material layer with a thickness of 80μm. Repeat the above steps on the other surface of the negative electrode current collector copper foil to obtain a negative electrode sheet with a double-sided negative electrode active material layer coated. After cold pressing, cutting and slitting, the negative electrode sheet is obtained.

[0179] <Preparation of positive electrode sheet>

[0180] The positive electrode active materials lithium cobalt oxide, conductive carbon black (Super P), and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 97:1.4:1.6, N-methylpyrrolidone (NMP) is added as a solvent and stirred evenly to prepare a positive electrode slurry with a solid content of 72wt%; the positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10μm, and dried at 85°C to obtain a positive electrode sheet coated with a positive electrode active material layer on one side, and the above steps are repeated on the other surface of the positive electrode current collector aluminum foil to obtain a positive electrode sheet coated with a positive electrode active material layer on both sides. Then, after cold pressing, cutting, and slitting, the positive electrode sheet is obtained, and the positive and negative electrode N / P ratio is set to 1.0, that is, the ratio of the negative electrode capacity per unit area to the positive electrode capacity per unit area is 1.0.

[0181] <Preparation of Electrolyte>

[0182] In a dry argon atmosphere glove box, ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC) are mixed in a mass ratio of 1:1:1 to obtain an organic solvent; lithium salt LiPF6 is dissolved in the above organic solvent, and then fluoroethylene carbonate (FEC) is added and mixed evenly to obtain an electrolyte. Among them, based on the total mass of the electrolyte, the mass percentage of LiPF6 is 12.5%, the mass percentage of FEC is 5%, and the balance is the organic solvent.

[0183] <Diaphragm>

[0184] A polyethylene (PE) film with a thickness of 7 μm was used as the separator.

[0185] <Preparation of lithium-ion batteries>

[0186] The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain an electrode assembly. After welding the pole ears, the electrode assembly is placed in an aluminum-plastic film packaging bag, placed in an 80°C vacuum oven for 12 hours to remove moisture, and the prepared electrolyte is injected. After vacuum packaging, standing, formation, degassing, trimming and other processes, a lithium-ion battery is obtained. The design potential range of lithium-ion batteries is 2.0V to 4.53V.

[0187] [Example 2] to [Example 4]

[0188] Compared with Example 1, except that in step (1) of <Preparation of Negative Electrode Materials> the raw materials of Example 2, Example 3 and Example 4 are SiO2 particles with a Dv50 of 300 nm, SiC particles with a Dv50 of 5 μm, and SiC particles with a Dv50 of 5 μm, respectively, and in addition, the asphalt coating oxidation times in Example 4 is 2 times, the rest are the same as Example 1.

[0189] [Example 5]

[0190] Compared with Example 1, except that in step (4) of <Preparation of Negative Electrode Material> a reducing atmosphere treatment is added after the halogen atmosphere treatment, specifically, a 5% hydrogen-argon mixture is further introduced for 3 hours to remove impurities, the rest is the same as Example 1.

[0191] Halogen atmosphere treatment In order to obtain a porous carbon structure, adding a reducing atmosphere treatment can further help the halide to escape, making the negative electrode material halogen-free.

[0192] [Example 6] to [Example 8]

[0193] Compared with Example 1, except that in step (1) of <Preparation of Negative Electrode Materials> the raw materials of Example 6, Example 7 and Example 8 are TiC particles with a Dv50 of 5 μm, B4C particles with a Dv50 of 5 μm, and W2C particles with a Dv50 of 5 μm, respectively, the rest are the same as Example 1.

[0194] [Comparative Example 1]

[0195] Except that the negative electrode active material is replaced by artificial graphite in <Preparation of Negative Electrode Sheet>, the N / P ratio of the positive and negative electrodes is set to 1.04, and the design potential range of the lithium ion battery is adjusted to 3.0V to 4.48V in <Preparation of Lithium Ion Battery>, the rest is the same as Example 1.

[0196] 3. Test Results

[0197] The relevant parameters and performance tests of each embodiment and each comparative example are shown in Table 1.

[0198]

[0199]

[0200] “ / ” in Table 1 indicates no relevant parameters.

[0201] From Examples 1 to 8 and the comparative examples, it can be seen that the introduction of different forms of porous carbon cores into the graphite skeleton can effectively increase the gram capacity of the negative electrode material. The porous carbon material formed by dehalogenation of carbides contributes to this part of the capacity. The porous carbon core obtained by suitable carbides can provide a higher capacity for the negative electrode material, thereby increasing the energy density of the secondary battery. The introduction of the porous carbon core effectively slows down the expansion of the graphite material in a long cycle and improves the capacity retention rate of the secondary battery.

[0202] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.

[0203] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0204] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A negative electrode material, characterized in that: The negative electrode material has an inner body and a layer structure wrapping the inner body, wherein: The inner body has a graphite skeleton and a porous carbon core arranged inside the graphite skeleton; The layer structure is a disordered carbon layer.

2. The negative electrode material according to claim 1, characterized in that The porous carbon core includes a plurality of porous carbon particles.

3. The negative electrode material according to claim 1, characterized in that The porous carbon core is a single porous carbon particle; Preferably, the graphite skeleton partially covers a single porous carbon particle, and preferably, a portion of the single porous carbon particle not covered by the graphite skeleton is arranged in contact with the disordered carbon layer; Preferably, the graphite skeleton completely covers a single porous carbon particle.

4. The negative electrode material according to claim 1, characterized in that The porous carbon core contains carbon elements; Preferably, the porous carbon core further comprises other elements, and the other elements include one or more of Ti, Si, B, Zr, Fe, Al, Mo, V, Nb, W, Ta, Cr, Sr, Ba and Ca; Preferably, the content A of the other elements in the porous carbon core is 0<A≤5%; Preferably, the porous carbon core comprises at least one of a carbide of the other element or a halide of the other element.

5. The negative electrode material according to claim 1, characterized in that The true density of the negative electrode material is 1.5 g / cm 3 Up to 2.0g / cm 3 .

6. The negative electrode material according to claim 1, characterized in that: The pore volume of the negative electrode material obtained by carbon dioxide adsorption and desorption test is ≤0.05cm 3 / g.

7. The negative electrode material according to claim 1, characterized in that: The negative electrode material satisfies at least one of the following conditions: (1) The Dv50 of the negative electrode material is 3 μm to 12 μm; preferably, the Dv50 of the negative electrode material is 5 μm to 9 μm; (2) The specific surface area of ​​the negative electrode material is 0.5 m 2 / g to 50m 2 / g; preferably, the specific surface area of ​​the negative electrode material is 0.5m 2 / g to 5m 2 / g; (3) In the Raman test, the negative electrode material has a Raman shift of 1300 cm -1 Up to 1400cm -1 The region contains a characteristic peak D with a peak intensity of ID and a Raman shift of 1530cm -1 Up to 1630cm -1 The region contains a characteristic peak G with a peak intensity of IG, and the peak intensity ratio ID / IG of the D peak to the G peak satisfies: 0.2≤ID / IG≤0.

7.

8. A method for preparing a negative electrode material, characterized in that: The following steps are involved: S10: All the porous carbon precursor powders to be coated are mixed with the initial asphalt powder to obtain an initial mixed powder, the initial mixed powder is heated to T1 and oxygen-containing gas is introduced to oxidize for t1 time to complete a heating oxidation coating treatment, the treated powder is collected, and the heating oxidation coating treatment is repeated multiple times, each time a new portion of asphalt powder is added to the treated powder collected in the previous time, and then heated and oxygen-containing gas is introduced to oxidize, until the oxidized asphalt powder coats the porous carbon precursor powder to a preset coating degree, to obtain asphalt-coated powder; S20: heating the asphalt-coated powder to T2 in an inert atmosphere and then performing heat preservation treatment, and cooling the temperature to room temperature in an inert atmosphere after heat preservation for t2 time to obtain carbonized powder; S30: heating the carbonized powder to T3 in an inert atmosphere and then performing heat preservation treatment, and cooling the temperature to room temperature in the inert atmosphere after heat preservation for t3 time to obtain graphitized powder; S40: heating the graphitized powder to T4 under an inert atmosphere and then keeping the temperature, introducing a halogen-containing atmosphere at T4 to perform etching for t4 time, then introducing an inert gas or a mixture of an inert gas and hydrogen to remove impurities, and finally cooling the temperature to room temperature under the inert atmosphere to obtain a graphite composite material containing a porous carbon core; S50: heating the graphite composite material to T5 under an inert atmosphere and then keeping the temperature, introducing an organic atmosphere at T5 for t5 time, and finally cooling the graphite composite material under an inert atmosphere to finally collect and obtain the negative electrode material.

9. The method for preparing the negative electrode material according to claim 8, characterized in that: Step S10 includes: Controlling the wrapping structure of the inner body in the negative electrode material by adjusting at least one of the ratio of the Dv50 value of the pitch powder to the Dv50 value of the porous carbon precursor powder, the mass ratio of all the porous carbon precursor powders to be wrapped to all the portions of the pitch powder, and the number of heating oxidation wrapping treatments; Preferably, the ratio of the Dv50 value of the asphalt powder to the Dv50 value of the porous precursor powder is 0.05 to 0.5; Preferably, the ratio of the Dv50 value of the pitch powder to the Dv50 value of the porous carbon precursor powder is greater than 0.5; In step S10, the porous carbon precursor powder includes at least one of oxides or carbides of Ti, Si, B, Zr, Fe, Al, Mo, V, Nb, W, Ta, Cr, Sr, Ba, and Ca; Preferably, the porous carbon precursor powder comprises SiO2; Preferably, the porous carbon precursor powder comprises SiC, TiC, B4C or W2C; Preferably, the porous carbon precursor powder is a nano powder, and the Dv50 of the porous carbon precursor powder is 0nm to 500nm, excluding the end point 0nm; Preferably, the porous carbon precursor powder is a micron powder, and the Dv50 of the porous carbon precursor powder is 1 μm to 20 μm; Preferably, in step S10, the asphalt powder Dv50 is 1 μm to 5 μm; Preferably, in the step S10, the porous carbon precursor powder is mixed with the pitch powder in a mass ratio of 100:1 to 30; Preferably, in step S10, the temperature T1 is 130° C. to 500° C., and the time t1 is 0.2 h to 12 h.

10. The method for preparing the negative electrode material according to claim 8, characterized in that: At least one of the following conditions is met: (1) In step S20, the temperature T2 is 600° C. to 1300° C., and the time t2 is 0.5 h to 5 h; (2) In step S30, the temperature T3 is 2000° C. to 3000° C., and the time t3 is 0.5 h to 12 h; (3) In the step S40, the temperature T4 is 300° C. to 1500° C., and the time t4 is 0.5 h to 36 h; (4) In the step S50, the temperature T5 is 400°C to 1000°C, and the time t5 is 0.5h to 36h.

11. The method for preparing the negative electrode material according to claim 8, characterized in that: In the step S40, the halogen-containing atmosphere includes at least one of F2, Cl2, Br2, I2, HF, CCl4, CHCl3, Cl2-H2, Cl2-HCl, and HCl.

12. A secondary battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the negative electrode sheet comprises a negative electrode collector and a negative electrode active material layer located on at least one surface of the negative electrode collector, and the negative electrode active material layer comprises the negative electrode material described in any one of claims 1 to 7 or the negative electrode material prepared by the preparation method described in any one of claims 8 to 11.

13. The secondary battery according to claim 12, characterized in that: The compaction density of the negative electrode active material layer is 1.1 g / cm 3 Up to 1.6g / cm 3 .

14. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to claim 12 or 13.

Citation Information

Cited By

  • Graded graphitization degree porous carbon material, silicon-carbon composite negative electrode material, preparation method and application

    CN121134759A